(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2020)
TITLE: Comparison of higher order aberrations in keratoconic eyes with regular high astigmatic eyes. PURPOSE: The purpose of the study is to quantify HOAs by comparing topometric measurement and anterior corneal aberrations in eyes with keratoconus and with regular high astigmatism using placido based topographer OBJECTIVE: To understand and correlate the value and type of aberration in regular as to keratoconic induced astigmatism. STUDY DESIGN: Cross sectional observational comparative study. METHODS: study performed on 30 eyes as per inclusion criteria with mild to moderate keratoconus with astigmatism >3.0D and 30 eyes with regular high astigmatism with astigmatism >3.0D. Topographic indices and the total corneal wavefront were measured by placido’s disc based topographer which measures aberrations using ray tracing techniques. The wavefront aberrations upto fourth order and low, high and total RMS were analysed and compared between these groups. 1 RESULTS: All topometric indices were higher in keratoconus eyes compared to regular high astigmatism eyes (P<0.01). Higher order aberrations in regular high astigmatic eye, oblique trefoil, vertical coma, spherical aberration and secondary astigmatism were -0.10±0.14, 0.01±0.15, 0.23±0.08 and -0.07±0.06 respectively which were significantly higher in keratoconic eyes as compared with regular high astigmatism as to 0.65±0.41, -1.17±0.85, -0.51±0.38 and 0.31±0.32 respectively (P<0.01). All RMS values were found increased in keratoconic eyes (P<0.01). No significant difference was found in lower order aberrations between both the groups (P>0.05). CONCLUSION:- Oblique trefoil, Vertical coma, Spherical aberrations and Secondary astigmatism aberrations may useful for differentiating regular high astigmatism verses irregular high astigmatic eye.